Is the Achievement Motive Gender-Biased? The Validity of TAT/PSE in Women and Men - Gruber, Nicole (Frontiers in Psychology, 2017)
In picture story exercises like the Thematic Apperception Test (TAT; Heckhausen, 1963), different pictures are presented to a person with the instruction to create a story using the scenes portrayed in the image. It is assumed, that people identify themselves with the people in the images and project their unconscious motives (e.g. achievement motive) onto them. As the TAT shows only men in the pictures, critics claimed the test is gender-biased; assuming women cannot identify with men in pictures. However, it was not assessed, whether female protagonists of the picture really trigger the same achievement motive as men. Therefore, two studies were conducted to address the gender difference and validity of the TAT using a version with only men in the pictures (study 1) or only women in the pictures (study 2). The results shows that the original TAT of Heckhausen is a valid instrument for women and men, but the modified version with only women in the pictures cannot validly measure the achievement motive in the male sample.